2009
DOI: 10.1007/s10531-009-9661-z
|View full text |Cite
|
Sign up to set email alerts
|

The importance of host tree age, size and growth rate as determinants of epiphytic lichen diversity in boreal spruce forests

Abstract: The amount of large and old trees has decreased in the boreal forests during the last centuries of forestry. Such trees are important habitats for epiphytic lichens and there is a growing concern for lichen species that are associated with large and old trees. However, only little is known about the relative importance of tree size versus age as determinants of lichen diversity. Here we have determined the size, age and growth rate of 157 Norway spruce trees and recorded the occurrence of epiphytic lichen spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(72 citation statements)
references
References 46 publications
2
62
1
2
Order By: Relevance
“…A large body of literature supports the view that tree-level factors are fundamental for explaining lichen richness at the scale of single tree (e.g. Lie et al 2009). However, our results support the idea that at this spatial scale local factors, indicative of environmental conditions, are also influential (see also Jüriado et al 2009) and interact with tree-level factors.…”
Section: Discussionmentioning
confidence: 91%
“…A large body of literature supports the view that tree-level factors are fundamental for explaining lichen richness at the scale of single tree (e.g. Lie et al 2009). However, our results support the idea that at this spatial scale local factors, indicative of environmental conditions, are also influential (see also Jüriado et al 2009) and interact with tree-level factors.…”
Section: Discussionmentioning
confidence: 91%
“…They found that retention of snags close to existing populations of red-listed species was more beneficial than an even, dispersed distribution. In another study, however, no detectable effect of hotspot landscapes with a documented rich fauna of red-listed beetles was found on the beetle fauna in high stumps (Lindbladh et al, 2007). In a follow-up study using window traps instead of bark sampling, a certain effect of hotspot surroundings could be seen for birch high stumps, but not for spruce high stumps .…”
Section: High Stumpsmentioning
confidence: 87%
“…The type of trees that are included in the retention groups may have a strong effect on species composition. Lie et al (2009) recommend that to maintain epiphytic flora, trees in retention groups should be large and old.…”
Section: Retention Patchesmentioning
confidence: 99%
“…The diameter of the tree is correlated to space availability for lichen species development and it is known as a key factor for community structure (Belinchon et al 2007). According to Lie et al (2009) it is possible that physical-chemical bark characteristics change with time and that an old substrate can provide a different substrate in a young tree.…”
Section: Discussionmentioning
confidence: 99%